Milton's peculiar grace : self-representation and authority - Fallon, Stephen M. (Ithaca : Cornell University Press, 2007)
"In Milton's Peculiar Grace, Fallon argues that Milton writes about himself to gain immortality, secure authority for his arguments, and exert control over his readers' interpretations. He traces the return of the repressed narrative of fallenness in the author's unacknowledged and displaced self-representations, which in turn account for much of the power of the late poems. Fallon's book, based on close readings of Milton's "self-constructions" in prose and poetry throughout his career, provides a new view of Milton's life and his importance for contemporary literary theory - in particular for continued questions about authorial intention."-- publisher
Self-representation, intention, and authority -- Interlude : the 1633 "Letter to a friend" -- The least of sinners : Milton in context -- "Himself before himself" : the early works -- "Kingdom of free spirits" : the anti-prelatical works -- "The spur of self-concernment" : the works on domestic liberty -- Interlude : interregnum poetry -- "It was I and no other" : interregnum prose -- "Elect above the rest" : De doctrina Christiana and Paradise lost -- "If all be mine" : confidence and anxiety in Paradise lost -- "I as all others" : Paradise regained and Samson Agonistes.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Milton, John, -- 1608-1674 -- Criticism and interpretation; Milton, John, -- 1608-1674 -- Criticism and interpretation; Milton, John, -- 1608-1674 -- Critique et interprétation.; Milton, John, -- 1608-1674; Milton, John; Self in literature; Autobiography in literature; Authority in literature; Moi (Psychologie) dans la littérature.; Autobiographie dans la littérature.; Autorité dans la littérature.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Authority in literature; Autobiography in literature; Self in literature; Selbstdarstellung; Zelfpresentatie; Criticism, interpretation, etc